Screening and surveillance of oesophageal varices in patients with HCV‐positive liver cirrhosis successfully treated by direct‐acting antiviral agents. (7th March 2022) - Ciancio, Alessia; Ribaldone, Davide Giuseppe; Salamone, Rossella; Bruno, Mauro; Caronna, Stefania; Debernardi Venon, Wilma; Giordanino, Chiara; Mondardini, Alessandra; Musso, Alessandro; Pennazio, Marco; Rolle, Emanuela; Sacco, Marco; et al.
Abstract: Background & Aims: limited evidence is available to guide hepatologists regarding endoscopic surveillance of oesophageal varices (EV) in Hepatitis C Virus (HCV)‐positive cirrhotic patients achieving a sustained virologic response. To address these issues, we conducted a long‐term prospective study on 427 HCV‐positive cirrhotic patients successfully treated by Direct Antiviral Agents (DAAs). Methods: Patients were divided into two groups according to their baseline Baveno VI status: Group 1 (92, 21.5%, favourable Baveno VI status) and Group 2 (335, 78.5%, unfavourable Baveno VI status). Each patient underwent baseline endoscopy and was endoscopically monitored for a median follow‐up of 65.2 months according to Baveno VI recommendations. Results: About 4.3% of Group 1 patients showed baseline EV compared with 30.1% of Group 2 patients ( p  < .0001). No patients belonging to Group 1 without baseline EV developed EV at follow‐up endoscopy compared with 6.5% in Group 2 patients ( p  = .02); 69/107 (64.5%) patients with baseline EV showed small varices. During the endoscopic follow‐up, EV disappeared/improved in 36 (33.6%), were stable in 39 (36.4%) and worsened in 32 (29.9%) patients, all belonging to Group 2 ( p  = .001). Improvement in Baveno VI status was observed in 118/335 (35.2%, p  < .0001) of Group 2 patients and among those without pre‐therapy EV, none developed EV throughout the follow‐up. Conclusions: HCV‐positive cirrhotic patients cured by DAAs showing baseline favourable Baveno VI status and no worsening during follow‐up can safely avoid endoscopic screening and surveillance. Patients having unfavourable Baveno VI status without baseline EV who improve their status may suspend further endoscopic surveillance.